2021
DOI: 10.1038/s41467-021-25785-z
|View full text |Cite
|
Sign up to set email alerts
|

Pegasus, a small extracellular peptide enhancing short-range diffusion of Wingless

Abstract: Small Open Reading Frames (smORFs) coding for peptides of less than 100 amino-acids are an enigmatic and pervasive gene class, found in the tens of thousands in metazoan genomes. Here we reveal a short 80 amino-acid peptide (Pegasus) which enhances Wingless/Wnt1 protein short-range diffusion and signalling. During Drosophila wing development, Wingless has sequential functions, including late induction of proneural gene expression and wing margin development. Pegasus mutants produce wing margin defects and pron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Having established the principle of lncRNA translation, first by experimentally proving the coding function of specific lncORFs 8 , 10 , 12 , 56 , 61 , 62 , and then by extending this finding to the genomic level 6 , 63 , 64 and this study), the next question is the actual molecular function of the translated ORFs, and which perform their cellular role at the level of encoded and translated micropeptides. We find that robustly translated lncORFs as a group contain clear evidence for the conservation of AA sequences, an indication that a good proportion of this cohort is exerting its function at the protein level.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Having established the principle of lncRNA translation, first by experimentally proving the coding function of specific lncORFs 8 , 10 , 12 , 56 , 61 , 62 , and then by extending this finding to the genomic level 6 , 63 , 64 and this study), the next question is the actual molecular function of the translated ORFs, and which perform their cellular role at the level of encoded and translated micropeptides. We find that robustly translated lncORFs as a group contain clear evidence for the conservation of AA sequences, an indication that a good proportion of this cohort is exerting its function at the protein level.…”
Section: Discussionmentioning
confidence: 95%
“…Our group has previously shown that standard homology-detection methods such as BLAST are not adequate for smORFs 1 . Based on successful experiences at detecting and experimentally corroborating smORF orthologues, including putative lncRNAs [8][9][10]20,56,57 , we have developed GENOR 1.0, a bioinformatic pipeline for smORF homology detection (Fig. 5a and 'Methods').…”
Section: Phylogenetic Conservation Supports Lncrna Translation and Mi...mentioning
confidence: 99%
“…Despite their abundance, only tens of shCDS genes have been characterised in Drosophila. These studies have shown that shCDS peptides mainly interact with canonical proteins and regulate their functions by diverse mechanisms (Pueyo et al, 2016a;Plaza et al, 2017), playing essential roles in signalling processes, organelle homeostasis and cytoskeleton dynamics (Pueyo et al, 2016b;Ding et al, 2017;Johnson et al, 2021;Magny et al, 2021). Importantly, many shCDS functions are conserved in humans and their mutations associated with pathogenesis (Pueyo et al, 2016a;Patraquim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%